Inorganic Aqueous Anionic Redox Liquid Electrolyte for Supercapacitors. Issue 4 (12th September 2021) - Pang, Le; Wang, Hongxia
Abstract: Energy storage system based on supercapacitors is known for its high power density but suffers low energy density. To address this issue, aqueous anionic redox liquid electrolyte (AARLE) has been explored to enhance the energy density of supercapacitors by taking advantage of AARLE's favorable features including fast transport of ions in the liquid medium and electrochemical charge transfer of the redox couple in the liquid electrolyte, which is expected to produce supercapacitors with desirable high density of energy and power. The past few years have witnessed the progress of AARLE in energy storage applications such as supercapacitors. Given the significant potential of AARLE in supercapacitors, in this article, the application of AARLE in different types of supercapacitors, including electrical double‐layer capacitors, pseudocapacitors, and asymmetric supercapacitors is reviewed. The performance of the supercapacitors that utilize AARLE with representative redox couple species such as Br − /Br3 −, I − /I3 −, I2 /IO3 −, S 2− /Sx 2−, Fe(CN)6 4− /Fe(CN)6 3− is summarized and systematically analyzed in terms of specific capacitance, energy density, power density, and cycling stability. The underlying mechanism of these representative anionic redox species is shown in supercapacitors. The advantages and disadvantages of each of these anionic redox species are discussed regarding delivering stable supercapacitors with high energy density and power density for practical applications. Finally, the challenge and opportunity of AARLE for supercapacitors are presented. It is hoped that this timely review on this critical topic can offer a new perspective for developing high‐performance supercapacitors by taking advantage of the anionic redox charge storage in the liquid electrolytes in the future. Abstract : The performance, applications, challenges, and opportunities of aqueous anionic redox liquid electrolyte are reviewed in different types of supercapacitors with representative anionic redox couple species including, Br − /Br3 −, I − /I3 −, I2 /IO3 −, S 2− /Sx 2−, Fe(CN)6 4− /Fe(CN)6 3− . The underlying mechanism, advantages, and disadvantages of these species in supercapacitors are discussed. This review provides insight for developing stable and practical supercapacitors with high energy density and power density for the future.